Faith ad The State: A History of Islamic Philanthropy in Indonesia - Hilman Latief (Pacific Affair, 2015)
For the past few decades, an enthusiasm to revitalize philanthropic practices has had far-reaching consequences to the increasing visibility of Islam in the Indonesian public space.